North American foreign missions, 1810-1914 : theology, theory, and policy - Shenk, Wilbert R. (Grand Rapids, MI, W.B. Eerdmans Publishing Company, 2004)
"The year 1810 marks the start of the North American foreign missions movement - a movement begun with typical American enthusiasm and vigor but in need of practical grounding. This volume explores important facets of the development of North American foreign missions, paying particular attention to the role that agencies such as the American Board of Commissioners for Foreign Missions played in shaping the theology, theory, and policy of evangelistic activities overseas. Distinguished by its special focus on key developments taking place at the home base, this set of insightful studies sheds light on significant yet neglected topics, including the impact of slavery debates on foreign missions, the emergence of distinctive mission strategies for women, the role of the social gospel as a missionary ideology, and the contribution of foreign missions to the creation of a global evangelical network."--Jacket.
The new divinity and the origins of the American Board of Commissioners for Foreign Missions / David W. Kling -- "A bright and new constellation" : millennial narratives and the origins of American foreign missions / Richard Lee Rogers -- Denominationalism and democracy : ecclesiastical issues underlying Rufus Anderson's Three self program / Paul Harris -- The 1845 organic sin debate : slavery, sin, and the American Board of Commissioners for Foreign Missions / Charles A. Maxfield III -- Evangelist or homemaker? : mission strategies of early nineteenth-century missionary wives in Burma and Hawaii / Dana L. Robert -- "The salvation of souls" and the "salvation of the Republic of Liberia" : denominational conflict and racial diversity in antebellum Presbyterian foreign missions / Susan Wilds McArver -- Forging an ideology for American missions : Josiah Strong and manifest destiny / Wendy J. Deichmann Edwards -- Canadian Presbyterians and India missions, 1877-1914 : the policy and politics of "women's work for women" / Ruth Compton Brouwer -- The social gospel as missionary ideology / Janet F. Fishburn -- Missionary returns and cultural conversions in Alabama and Shandong : the latter years of Madam Gao (Martha Foster Crawford) / Carol Ann Vaughn -- The development of the missionary ideas of Robert E. Speer / John F. Piper, Jr. -- Only connect : the China Inland Mission and transatlantic evangelicalism / Alvyn Austin.
"The majority of the chapters ... were originally delivered at two consultations of the North Atlantic Missiology Project (NAMP) which took place at the University of Wisconsin--Madison in November 1997 and Fuller Theological Seminary, Pasadena, California, in March 1998"--General editors' pref.
Includes bibliographical references (pages 314-339) and index.
Keywords: American Board of Commissioners for Foreign Missions -- History; Missions, American; Conference papers and proceedings